The Single Candidate in the 2020 Regional Head Election is Viewed From the Perspective of Democratic Principles Adopted by the Indonesian State - Shintamy Nesyicha Syahril; Ahmad Redi (International Journal Labs, 2023)
The development of Indonesia's governance is currently quite rapidly developing. Indonesia is one of the countries that adheres to a democratic system. This understanding is elaborated constitutionally and fundamentally in the Preamble to the NRI Constitution of 1945 Alenia IV, which affirms one of the country's policies which reads: